2009
DOI: 10.1590/s1517-83822009000200002
|View full text |Cite
|
Sign up to set email alerts
|

CLSI broth microdilution method for testing susceptibility of Malasseziapachydermatis to thiabendazole

Abstract: Thiabendazole, classified as antiparasitic and also used as an antifungal drug, can be found as otological solution indicated for treatment of parasitic and fungal external otitis in small animals. Malassezia pachydermatis is a yeast recognized as a normal inhabitant on the skin and mucous membranes of dogs and cats. However, it is considered an opportunistic agent that causes external otitis and dermatitis in these animals. The aim of this study was to evaluate the in vitro effect of thiabendazole against 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
(26 reference statements)
0
34
1
Order By: Relevance
“…In clinical practice, recurrent Malassezia otitis is commonly reported, and failure of treatments to control yeast overgrowth is often attributed to ‘resistance’ to the antifungal employed, with a consequent switch to another principle. This practice may be influenced by published studies that reported isolates of M. pachydermatis resistant to various azoles 6–8 . Resistance is defined as the reduction in effectiveness of an antimicrobial drug in curing an infectious disease 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, recurrent Malassezia otitis is commonly reported, and failure of treatments to control yeast overgrowth is often attributed to ‘resistance’ to the antifungal employed, with a consequent switch to another principle. This practice may be influenced by published studies that reported isolates of M. pachydermatis resistant to various azoles 6–8 . Resistance is defined as the reduction in effectiveness of an antimicrobial drug in curing an infectious disease 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously published data regarding the in vitro antifungal susceptibility of M. pachydermatis using various types of assays are conflicting. Using a disk diffusion test, total resistance to TBD was reported, 18 while in another study, most isolates of the yeast were found to be susceptible to this agent 8 . Disk diffusion assays of CTZ and MCZ also yielded conflicting results, with some authors reporting resistant isolates 6,7 and other studies finding that these drugs had substantial activity 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…MIC of the plant and fungal extracts along with the standard drug Fluconazole was determined by NCCLS Broth Microdilution (BM) method on sterile microtiter plate with 96 flat bottomed (Nascente et al, 2009) with slight modifications. The C. albicans isolate was suspended in saline solution with the turbidity adjusted to level 1 of the McFarland scale.…”
Section: Determination Of Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…, and seven clinically isolated MDR strains of A. baumannii (AB293) were used for this study. We followed the Clinical and Laboratory Standards Institute (CLSI) standardized method for broth microdilution with some modifications [46]. Briefly, bacteria were subcultured on Luria-Bertani (LB) agar plates (Lab M, UK) overnight and grown in Müller-Hinton (MH) broth (Lab M, UK) for 24 h. The turbidity of the bacterial suspension was adjusted to level 0.5 of the McFarland scale.…”
Section: Antibacterial Susceptibility Testmentioning
confidence: 99%